The Backup Recovery Strategy Selection to Maintain the Business Continuity Plan - Faisal Faisal (Journal of Applied Sciences and Advanced Technology, 2018)
Indonesia must face the risks of volcanic eruptions, earthquakes, floods and tsunamis, destruction of its land areas, and resulting in damage to client and server computer systems. The demand for the information technology availability and performance becomes high. Disaster recovery plan is designed to ensure the vital business processes continuation in the event that a disaster occurs. The problem is how to make the best way in selecting backup recovery strategy based on the benefits to the cost ratio so as to minimize the business losses that will be caused by the failure of an application system. The research aims to make decisions that can help make certain parties take the best decision in choosing the backup recovery strategy selection for a business continuity plan in the University Trilogy. The method used is the multi-criteria decision making and analytical hierarchy process using the expert choice software. From the data processing results can be concluded that the first order is hot standby option 59.4%, followed by cold standby option 23.3%, then the choice of warm standby option 17.4%. The data inconsistency rate is 0.02, smaller than 0.1 as the maximum value of inconsistency ratio.